Teacher’s Manners Towards Students Perspective of KH. Hasyim Asy’ari (in The Book Adab Al-‘Alim Wa Al-Muta’allim) - Asiah, Siti; Isnaeni, Muflihatul; Nurazizah, Indah; Malika, Elisa; Masturoh, Zahrani; Putri, Tania Amanda (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
One of the problems that occur in the world of education today is related to a teacher's behavior towards his students. Where, a teacher should set an example of good things, in reality he behaves poorly so that he is unable to take responsibility for the duties and mandate given. The aim of the research was to find out and study further regarding teachers' manners towards students in the book Adab Al-'Alim Wa Al-Muta'allim by KH. Hasyim Asy'ari. The research method uses a qualitative approach in literature through the Book of Adab Al-'Alim Wa Al-Muta'allim by KH. Hasyim Asy'ari which has been translated into Indonesian and through journals and books available on the internet. Stages of research by collecting various kinds of references, then study further and draw conclusions. As for the result of this research is that a teacher must understand the real task and his true role. Because there has been a code of ethics and Law No. 14 of 2005 concerning teachers and lecturers as professional positions. Teacher's duties as good mentor and teacher of students, therefore it is mandatory to be a role model for students both in terms of science, nature, etiquette even his devotion to Allah SWT.